Z badań nad przesłankami fermentu intelektualnego w Królestwie Polskim bezpośrednio po powstaniu styczniowym - Markiewicz, Grzegorz (Acta Universitatis Lodziensis. Folia Historica, 1998)
Although policy of tsarism towards Poland was not favourable to any intellectual movement, a progressive intellectual leaven could be seen shortly after the January Insurrection of 1863. Development of intelligentsia, press, publishing business and sciences became favourable for it. Warsaw became a main center of intellectual life. The intellectual leaven was undoubtedly based on changes in Polish reality. Patterns of ideas were transmited from West-European thinkers. Although first signs of the leaven could be seen before 1863, but philosophy of positivism popularized in 1860s and 1870s gave it a new sense. However a vivacious intellectual movement did not rise new problems or questions, answers given during debates and polemics made for an intellectual revolution. The problems which were risen concerned idea of the world and the man as well as man’s place in nature and in society; laws of nature, society and history, limits for human knowledge, science and religion. They concerned also ethical and aesthetical attitudes and first of all philosophy of life, proper for Polish society.